2020
DOI: 10.5761/atcs.oa.19-00314
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Predictors and Long-Term Mortality of New-Onset Postoperative Atrial Fibrillation Following Isolated Aortic Valve Replacement Surgery

Abstract: Purpose: Postoperative atrial fibrillation (POAF) after coronary artery bypass grafting (CABG) has been associated with increased risk of death in women but not in men. We aimed to explore predictors and long-term mortality in POAF following isolated aortic valve replacement (AVR) surgery in men and women. Methods: This study included 379 severe aortic stenosis patients with no prior atrial fibrillation (AF) who underwent isolated AVR surgery. We used multiple logistic regression to investigate independent gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Fragão-Marques et al [32] conducted a study of 379 patients who underwent isolated AVR surgery. They used multiple logistic regression to look at gender-specific predictors of POAF and found an independent association between increased postoperative peak lactate and POAF in men and a lower mean aortic valve gradient with POAF in women (area under the curve (AUC) for the model = 0.77 [0.68-0.86] and 0.69 [0.60-0.78] for men and women, respectively) [32]. At a 4-year followup Fragão-Marques et al [32] found that POAF was linked to increased risk of death in men but not in women.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Fragão-Marques et al [32] conducted a study of 379 patients who underwent isolated AVR surgery. They used multiple logistic regression to look at gender-specific predictors of POAF and found an independent association between increased postoperative peak lactate and POAF in men and a lower mean aortic valve gradient with POAF in women (area under the curve (AUC) for the model = 0.77 [0.68-0.86] and 0.69 [0.60-0.78] for men and women, respectively) [32]. At a 4-year followup Fragão-Marques et al [32] found that POAF was linked to increased risk of death in men but not in women.…”
Section: Gendermentioning
confidence: 99%
“…They used multiple logistic regression to look at gender-specific predictors of POAF and found an independent association between increased postoperative peak lactate and POAF in men and a lower mean aortic valve gradient with POAF in women (area under the curve (AUC) for the model = 0.77 [0.68-0.86] and 0.69 [0.60-0.78] for men and women, respectively) [32]. At a 4-year followup Fragão-Marques et al [32] found that POAF was linked to increased risk of death in men but not in women. Conflicting results were obtained by Filardo et al [33] who discovered that the effect of POAF on long-term survival after CABG surgery did not differ between the sexes.…”
Section: Gendermentioning
confidence: 99%
“…Notably, this was observed despite more severe AS based on echocardiographic indices and higher incidence of hypertension recorded in women, both common factors associated with worst prognosis in AS patients [ 53 , 54 ]. Similarly, another study, which included 379 patients with severe AS and with no prior atrial fibrillation, who underwent isolated AVR surgery, reported sex-related differences in factors linked to post-operative atrial fibrillation and its impact on mortality, with an increased risk of death observed in men but not in women [ 55 ]. Moreover, at 4-year follow-up, post-operative atrial fibrillation was associated with the increased risk of death only in men.…”
Section: Sex-related Differences Of Calcific Aortic Valve Stenosismentioning
confidence: 99%
“…It was assessed through telemetry and EKG recordings, as well as doctors’ and nurses’ records, as previously described. 15 Gathered data was introduced in a coded database.…”
Section: Methodsmentioning
confidence: 99%